The People's Republic of China's small and medium enterprise development strategies in the context of a national innovation system - Tracy Yang; Jamus Jerome Lim; Toshiki Kanamori (Asian Development Bank Institute (ADBI), 2006)
With deregulation and globalization, and the direct impact of these developments on economies worldwide, it is necessary for authorities in the People's Republic of China (PRC) to consider an approach that would further attune its economic engine toward sustained growth. This paper argues that certain industries-in particular, the small and medium enterprise (SME) sector-may play a significant role in terms of any further reforms of the PRC's National Innovation System. It highlights how issues such as innovation, R&D, and strategic clustering may influence the SME sector, and outlines both internal as well as external conditions that may impact any further development of this sector.
Keywords: O32; O53; P31; 330; SME; National Innovation System; network cluster; the PRC